Similarities and differences in the biotransformation and transcriptomic responses of Caenorhabditis elegans and Haemonchus contortus to five different benzimidazole drugs. (December 2019) - Stasiuk, S.J.; MacNevin, G.; Workentine, M.L.; Gray, D.; Redman, E.; Bartley, D.; Morrison, A.; Sharma, N.; Colwell, D.; Ro, D.K.; Gilleard, J.S.
Abstract: We have undertaken a detailed analysis of the biotransformation of five of the most therapeutically important benzimidazole anthelmintics - albendazole (ABZ), mebendazole (MBZ), thiabendazole (TBZ), oxfendazole (OxBZ) and fenbendazole (FBZ) - in Caenorhabditis elegans and the ruminant parasite Haemonchus contortus. Drug metabolites were detected by LC-MS/MS analysis in supernatants of C. elegans cultures with a hexose conjugate, most likely glucose, dominating for all five drugs. This work adds to a growing body of evidence that glucose conjugation is a major pathway of xenobiotic metabolism in nematodes and may be a target for enhancement of anthelmintic potency. Consistent with this, we found that biotransformation of albendazole by C. elegans reduced drug potency. Glucose metabolite production by C. elegans was reduced in the presence of the pharmacological inhibitor chrysin suggesting that UDP-glucuronosyl/glucosyl transferase (UGT) enzymes may catalyze benzimidazole glucosidation. Similar glucoside metabolites were detected following ex vivo culture of adult Haemonchus contortus . As a step towards identifying nematode enzymes potentially responsible for benzimidazole biotransformation, we characterised the transcriptomic response to each of the benzimidazole drugs using the C. elegans resistant strain CB3474 ben-1(e1880)III . In the case of albendazole, mebendazole, thiabendazole, and oxfendazole the shared transcriptomic response was dominated by the up-regulation of classical xenobiotic response genes including a shared group of UGT enzymes ( ugt -14/25/33/34/37/41/8/9). In the case of fenbendazole, a much greater number of genes were up-regulated, as well as developmental and brood size effects suggesting the presence of secondary drug targets in addition to BEN-1. The transcriptional xenobiotic response of a multiply resistant H. contortus strain UGA/2004 was essentially undetectable in the adult stage but present in the L3 infective stage, albeit more muted than C. elegans . This suggests that xenobiotic responses may be less efficient in stages of parasitic nematodes that reside in the host compared with the free-living stages. Graphical abstract: Image 1 Highlights: C. e. & H. c. display hexose conjugation (likely glucose) and excretion of 5 BZs. C. elegans (C.e.) biotransformation of ABZ reduces drug potency. UGT inhibitor chrysin reduces ABZ biotransformation by C. elegans . Transcriptomic response of C. e. (ben-1) to 5 BZs dominated by xenobiotic response and additional targets for FBZ. Minimal transcriptomic response of H. contortus to ABZ exposure.